Threat Analysis of Social Media Use on the Tendency of College Student Radicalism - Abshari, Hana (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Various complex aspects influence a person's formation of radical ideology. Several factors, such as a low sense of tolerance and national identity, are thought to encourage the entry of radicalism. In addition, the use of social media also increases the potential for radicalism because it is used as a new jihad medium by radical terror groups. On the other hand, college students, as part of the youth often exposed to social media, become potential targets. This study employs a mixed-method approach to explore the relationship between tolerance, national identity, and social media usage with radicalism and to identify emerging threats. Data was collected through questionnaires distributed to 150 Science students at the University of Indonesia and interviews with informants, including academics, policymakers, and practitioners. The results of hypothesis testing showed a low negative effect on tolerance and national identity. In contrast, using social media positively and moderately affects student radicalism. Social media’s freedom to share information and facilitate interaction makes it highly effective for spreading radical propaganda. This is coupled with the ability of radical terror groups to create narratives based on negative issues against the government. Other opportunities arise from students' insufficient deterrence power and loopholes in violating the law. A comprehensive prevention strategy is required to minimize potential threats through commitment and synergy from all elements of society.